Techniques of the educational inspection (I): the observation - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2013)
The observation provides information about a situation as it happens, this being his main potential, demanding an adequate degree of systematization and thoroughness both instruments are used as the agent that applies. Therefore, from the study of several possible definitions and conceptualizations, and their variants look the linkages of all with the educational inspection. Also reflect on the elements present in the observation, ie, the agent, the status and recording instrument. It is also important to dwell on the features that both general and specific fulfilled by the observer, who is inspector education and it presupposes a technical-normative. Will be analyzed also applying certain strategies to start and processes that may develop during the course of the observations. Finally, we conclude with the definitions, classifications and examples of assessment instruments given by the authors and can be used to make records of the observations made in the field of educational inspection.